Simple and efficient synthesis of 2-Aryl-2,3-dihydroquinolin-4(1H)-ones using silica chloride as a new catalyst under solvent-free conditions - Muthukrishnan, Murugan; Mujahid, Mohammad; Punitharasu, V.; Dnyaneshwar, D. A. (Synthetic Communications, 2010)
A mild, efficient, and high-yielding method for the synthesis of 2-aryl-2,3-dihydroquinolin-4(1H)-ones from their corresponding 2-amino chalcones using silica chloride (SiO2Cl) under solvent-free conditions is described. A series of 2-aryl-2,3-dihydroquinolin-4(1H)-ones containing both electron-donating and electron-withdrawing substituents were synthesized.
Keywords: 2-Amino chalcones; 2-aryl-2; 3-dihydroquinolin-4(1H)-ones; Microwave; silica chloride

Syntheses and biological evaluation of new triazole-spirochromone conjugates as inhibitors of mycobacterium tuberculosis - Muthukrishnan, Murugan; Mujahid, Mohammad; Yogeeswari, P.; Sriram, D. (Tetrahedron Letters, 2011)
A series of novel 1,2,3-triazole fused spirochromone conjugates have been synthesized bearing both spirochromone moiety as well as a 1,2,3-triazole moiety. Some of the compounds have exhibited potential activity against Mycobacterium tuberculosis (virulent strain H37Rv). In particular 5e proved to be the most potent derivative exhibiting MIC = 0.78 mu g/mL. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Antitubercular activity; Click chemistry; Mycobacterium tuberculosis; Spirochromones

Synthesis and antitubercular activity of amino alcohol fused spirochromone conjugates - Mujahid, Mohammad; Gonnade, Rajesh G.; Yogeeswari, P.; Sriram, D.; Muthukrishnan, Murugan (Bioorganic & Medicinal Chemistry Letters, 2013)
A series of 21 new amino alcohol fused spirochromone conjugates have been synthesized, characterized with analytical data and evaluated their antimycobacterial activity against Mycobacterium tuberculosis (virulent strain H37Rv) in vitro. Some of the compounds exerted significant inhibition, in particular, compound 4f found to be the most potent derivative exhibiting MIC = 3.13 mu g/mL. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Amino alcohol; Antitubercular activity; Mycobacterium tuberculosis; Spirochromones